Smartphone Addiction and Personality: Review of International Research - Viktor P. Sheinov (Peoples' Friendship University of Russia (RUDN University), 2021)
Mobile phones are perhaps the most popular digital devices that accompany us all the time. Smartphones certainly provide us with many conveniences but at the same time these devices are the reason why many users develop a pathological condition known as nomophobia or smartphone addiction, i. e., fear of losing phone contact or being away from network coverage. Many people, especially teenagers and children, cannot imagine their life without smartphones and try never to part with them. Phone addicts, due to the fact that their attention is constantly riveted to the smartphone screen, cannot efficiently study, do work thoughtfully and productively, establish relationships with others and, in general, live a full-fledged life. Smartphone addiction is a new phenomenon, one of the most widespread non-medical addictions, which in its scale has already left behind Internet addiction and addiction to gambling, forming a dangerous conglomerate with them. Numerous studies show that smartphone addiction has a detrimental effect on many important aspects of modern life. The purpose of this article is to provide an analytical review of international studies on the relationship between smartphone addiction and psychological and socio-psychological characteristics of personality. The choice of international studies as the initial data for the analysis was made due to the fact that it was in them (much earlier than in Russian ones) that the largest number of empirical results were obtained, which are of significant theoretical and practical interest. The number of Russian studies on this topic is much smaller, while many of them were carried out on small samples or were only discussions of international research results. Thus, it can be stated that the extensive information accumulated by international researcher on the dependence on smartphones is used insufficiently in Russian scientific community. The smartphone addiction is positively associated with such negative factors as depression, anxiety, stress, decreased self-esteem and self-control, sleep and health problems, low quality of life and dissatisfaction with it, family problems, poor school performance and the danger of becoming a victim of cyberbullying. Much higher smartphone addiction is typical of younger users. Assessments of smartphone dependence are positively correlated with being female, with smoking and consuming alcohol. A serious obstacle to relevant Russian research was the lack of Russian-language measuring instruments. To eliminate this obstacle, the author adapted and validated The Smartphone Addiction Scale (SAS) by M. Kwon et al. for the Russian-speaking society, and developed a reliable and valid Short Version of the Smartphone Addiction Questionnaire. In Russian studies on smartphone addiction, the results obtained on international samples can serve as basis for working hypotheses as well as initial data in cross-cultural research.